Bad machinery. Volume six, The case of the unwelcome visitor - Allison, John, 1976- (Allison, John, 1976- Bad machinery, 2016)
"School is out for summer, and for the Tackleford mystery team, that means lazy days, balmy evenings, and ... creeping existential dread that threatens the whole city. With half the team gallivanting off to exotic locales (like Aunty Kath's in Margate), can Linton, Jack, and Lottie solve this season's most dire case?"--Back cover.